Planetary mine : territories of extraction under late capitalism. - Arboleda, Martín (Verso Books, 2020)
"Planetary Mine rethinks the politics and territoriality of resource extraction, especially as the mining industry becomes reorganized in the form of logistical networks, and East Asian economies emerge as the new pivot of the capitalist world-system. Through an exploration of the ways in which mines in the Atacama Desert of Chile-the driest in the world-have become intermingled with an expanding constellation of megacities, ports, banks, and factories across East Asia, the book rethinks uneven geographical development in the era of supply chain capitalism. Arguing that extraction entails much more than the mere spatiality of mine shafts and pits, Planetary Mine points towards the expanding webs of infrastructure, of labor, of finance, and of struggle, that drive resource-based industries in the twenty-first century"--